1970
DOI: 10.1254/jjp.20.253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Ethoxycarbonyl-3-Mqrpholinosydno-Nimine (Sin-10) on the Cardiovascular System

Abstract: Sydnonimine derivatives, a series of mesoionic compounds, have a peculiar feature in their molecular structure and biological activities. The smooth muscle relaxing action of the compounds has been reported on the rat duodenum and the guinea-pig ileum by Oehme et al. (1) and hypotensive effect by Daeniker and Druey (2).Recently, 3-substituted sydnonimines were newly synthetized (3) and were found to have potent vasodepressor activities (4, 5). Of these compounds, a derivative, whose imino radical at 5 position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In isolated, perfused dog hearts, Takenaka et al (13) observed that intracoronary SIN 10 1 mg did not exert any appreciable changes in perfusion pressure, coronary blood flow, myocardial contractile force, heart rate, myocardial oxygen consumption and redox potentials. It can be assumed, therefore, that the fall in peak LV dp/dt during the hypo tension by SIN-10 might be caused from a fall in aortic pressure and stroke volume.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated, perfused dog hearts, Takenaka et al (13) observed that intracoronary SIN 10 1 mg did not exert any appreciable changes in perfusion pressure, coronary blood flow, myocardial contractile force, heart rate, myocardial oxygen consumption and redox potentials. It can be assumed, therefore, that the fall in peak LV dp/dt during the hypo tension by SIN-10 might be caused from a fall in aortic pressure and stroke volume.…”
Section: Discussionmentioning
confidence: 99%
“…The antianginal effects of molsidomine probably are due to a reduction in external cardiac work resulting from diminished preload and -to a lesser degree -afterload. More previously, Takenaka et al (16) have shown that molsidomine did reduce mean coronary flow in isolated hearts with changing perfusion pressures. The fall in coronary flow after molsidomine was not accompanied by changes in coronary sinus blood oxygen content so that the flow reduction most likely reflects the consequences of reduced myocardial oxygen demand.…”
Section: Discussionmentioning
confidence: 90%
“…The hemodynamic response to molsidomine in patients with un complicated myocardial infarction is charac terized by a marked reduction in right atrial and pulmonary capillary wedge pressures [ 10], which suggests that there is probably a concomitant reduction in ventricular dia stolic volumes. Indeed, a number of experi mental [16,20,21] and clinical studies [5,7,9,22] have suggested a pronounced and sus tained venodilating activity of molsidomine, which is associated with decreased ventricu lar filling pressures as well as decreased dia stolic and systolic ventricular dimensions. Thus, it is probable that molsidomine causes more reduction of left ventricular wall ten sion and further decrease in myocardial oxy gen requirements than can be explained by the fall in arterial pressure alone.…”
Section: Discussionmentioning
confidence: 99%